Konsep Penilaian Kinerja Karyawan Berbasis Akhlak - Andini Ayu Larasati; Veithzal Rivai Zainal; Lenny Christina Nawangsari (Publikasi Indonesia, 2022)
The code of conduct is a very important tool in realizing and creating working relationships based on the Company's Core Values (AKHLAK). It guarantees the maintenance of good cooperation, the creation of work comfort, business peace, business certainty, and regulates the rights and obligations of workers. Based on this, the Company's Code of Conduct was prepared with the aim of creating harmonious working relationships in order to improve quality and productivity to the maximum. Therefore, the Code of Conduct contains guidelines that become the basis for each employee in working which are prepared to influence, determine, regulate and carry out behavioral conformity so as to achieve consistent results in line with the Core Values of BUMN. Therefore, it is necessary to create a comprehensive measurement tool as a basis for assessing employee performance that can support overall company performance.